Effect of levothyroxine supplementation on pregnancy outcomes in women with subclinical hypothyroidism and thyroid autoimmuneity undergoing in vitro fertilization/intracytoplasmic sperm injection: an updated meta-analysis of randomized controlled trials - Meng Rao; Zhengyan Zeng; Shuhua Zhao; Li Tang (BMC, 2018)
Abstract Background Evidence suggests that subclinical hypothyroidism (SCH) and thyroid autoimmunity (TAI) are associated with adverse pregnancy outcomes. This systematic review and meta-analysis was conducted to determine whether levothyroxine (LT4) supplementation would improve pregnancy outcomes among infertile women with SCH and/or TAI who underwent in vitro fertilization (IVF) or intracytoplastic sperm injection (ICSI). Methods We searched databases of PubMed, EMBASE, Web of Science, Cochrane Controlled Trials Register databases, and Clinicaltrials.gov up to April 2018 to identify eligible studies. Studies that focused on the treatment effect of LT4 on pregnancy outcomes of women with SCH and/or TAI who underwent IVF/ICSI were included in the data synthesis. We only included randomized controlled trials (RCTs). Relative risks (RR) and 95% confidence intervals (CI) were calculated using a random-effects model to assess the results of pregnancy outcomes, including clinical pregnancy rate, miscarriage rate, live birth rate and preterm birth rate. Results Four published RCTs including 787 infertile couples undergoing IVF/ICSI were included in this meta-analysis. Notably, the study observed no significant associations of LT4 treatment with the clinical pregnancy rate (RR = 1.46, 95% CI: 0.86-2.48), live birth rate (RR = 2.05, 95% CI: 0.96-4.36), or preterm birth rate (RR = 1.13, 95% CI: 0.65-1.96). However, patients receiving LT4 supplementation had a significantly decreased miscarriage rate relative to those receiving a placebo or no treatment (RR = 0.51, 95% CI: 0.32-0.82). A further sub-group analysis showed that LT4 supplementation did not improve the miscarriage rates among patients with SCH (RR = 0.67, 95% CI: 0.39-1.15) or TAI (RR = 0.28, 95% CI: 0.07-1.06). Conclusions Given its potential to reduce the miscarriage rate, LT4 supplementation is recommended for infertile women with SCH and/or TAI who are undergoing IVF/ICSI. However, additional population-based RCTs are needed to confirm this recommendation.